UMP participation in SIFF 2015 - Nor Ilma, Mustafa Kamal (Penerbit UMP, 2015)
Universiti Malaysia Pahang (UMP) submitted three entries to the Seoul Invention and International Fair which was held from November 26-28, 2015.